Fear as the main feature of epileptic seizures. Issue 2 (1st February 2001) - Biraben, A; Taussig, D; Thomas, P; Even, C; Vignal, J P; Scarabin, J M; Chauvel, P
Abstract : OBJECTIVES: There are circumstances in which partial seizures may be misdiagnosed as acute psychiatric disturbances. In particular, when fear is the prominent feature the patient may be considered for years as having panic attacks. Eight patients in whom fear was the main symptom of the seizures are reported on. Patients who had a proved lack of consciousness during the fits and patients in whom fear was just fear of having a seizure were excluded. The ictal involvement of temporal limbic and frontal structures in those patients with fear of particular intensity was studied. METHODS: The localisation of the epileptogenic zone was assessed by prolonged interictal EEG recordings as well as ictal video-EEG recording of at least one seizure in every patient; five had ictal SPECT and four had chronic stereotactic implantation of depth electrodes (SEEG). In six patients, a cortical resection was performed with an Engel's class 1 outcome (minimum 28 months follow up, except for two patients). RESULTS: Localisations of primary epileptogenic zones were right temporal in three patients, left temporal in three, bitemporal in one, and frontal in one. In all cases, diagnosis of epileptic seizures could be clinically evoked because of the stereotypy of fits and of associated symptoms. The association of a fear sensation, autonomic symptoms, and coordinated behaviour suggests disturbance of a particular system. The SEEG data argue for temporolimbic and prefrontal lobe involvement in the expression of ictal fear. CONCLUSIONS: In intense ictal fear, with coordinated behaviour and autonomic features, the discharge may involve or interfere with a physiological complex information processing network. This network involves orbitoprefrontal, anterior cingulate, and temporal limbic cortices.